Pengaruh Paclobutrazol Terhadap Jumlah Klorofil, Umur Berbunga, dan Umur Panen Dua Varietas Sorgum (Sorghum bicolor (L.) Moench) - Amelia Aztrina; Luthfi A. M. Siregar; E. Harso Kardhinata (Universitas Sumatera Utara, 2014)
The objective of this research was to know effect of paclobutrazol to the number of chlorophyl,flowering time, and harvesting time of two sorghum varieties. This research was conducted inexperimental field at Jl. Pasar I Tanjung Sari, Medan from October 2013-January 2014,used randomized block design with two factors paclobutrazol concentration (0 g/l, 0,50 g/l,0,75 g/l, and 1 g/l) and varieties (Kawali and Numbu). Parameters measured were the number ofchlorophyl, flowering time, and harvesting time. The result showed that paclobutrazol affectedsignificantly on plant height, stem diameter, and flowering time. Varieties have significant differenton the number of chlorophyl, flowering time, and harvesting time.The interaction of the two factorsnot affected significantly on all parameters. There was no interaction between paclobutrazolconcentration and varieties to all parameters measured.Keywords: paclobutrazol, variety, sorghum